1989
DOI: 10.1063/1.101656
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow recombination velocity at Ga0.5In0.5P/GaAs heterointerfaces

Abstract: Using time-resolved photoluminescence, we have examined the optoelectronic properties of Ga0.5In0.5P/GaAs/Ga0.5In0.5P double heterostructures grown by organometallic chemical vapor deposition. For comparison, similar structures using Al0.4Ga0.6As/GaAs and Al0.5In0.5P/GaAs lattice-matched heterointerfaces were also examined. For the Ga0.5In0.5P/GaAs heterostructure, we show that the recombination velocity at a Ga0.5In0.5P/GaAs interface can be less than 1.5 cm/s. As a result, photoluminescence decay times as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(85 citation statements)
references
References 17 publications
2
82
0
1
Order By: Relevance
“…The Ga 0.5 In 0.5 P/GaAs twojunction solar cell, invented and developed at NREL, has achieved high efficiencies of around 30% [1][2][3] and is in large-scale production [4,5]. We have shown that very low (as low as 1.5 cm/s [6]) interface recombination velocities (IRV) can be achieved for the Ga 0.5 In 0.5 P/GaAs interface. However, in actual device structures, much higher IRVs are often observed.…”
Section: Introductionmentioning
confidence: 99%
“…The Ga 0.5 In 0.5 P/GaAs twojunction solar cell, invented and developed at NREL, has achieved high efficiencies of around 30% [1][2][3] and is in large-scale production [4,5]. We have shown that very low (as low as 1.5 cm/s [6]) interface recombination velocities (IRV) can be achieved for the Ga 0.5 In 0.5 P/GaAs interface. However, in actual device structures, much higher IRVs are often observed.…”
Section: Introductionmentioning
confidence: 99%
“…17 Note that since vertical diffusion over a distance larger than the effective depth of field of the microscope objective results in a defocused luminescence spot, The spectra in Fig. 1 are obtained via a 50 m diameter optical fiber whose diameter corresponds to a spot of diameter l ~ 1 m on the images of Fig.…”
Section: Textmentioning
confidence: 99%
“…1) are two popular materials for high efficiency solar cells. It has been found that many materials, such as AlGaAs and GaInP, [2][3][4][5][6] provide sufficient carrier confinement to GaAs, which prevents carriers from reaching the top surface of the epilayers and thus effectively reduces the surface recombination rate by providing a heterojunction interface. The interface recombination velocity (IRV) of a high quality GaAs/Al 0.5 Ga 0.…”
mentioning
confidence: 99%